Youth and Memory in Europe Defining the Past, Shaping the Future - Krawatzek, Félix; Friess, Nina (Media and Cultural Memory / Medien und kulturelle Erinnerung, 2022)
What kind of historical narratives are young people exposed to and what do they make of them? This volume brings together humanities and social sciences scholars in a study of youth and memory in different European regions. It explores the connections between the historical narratives expressed by young people and the broader, multifaceted historical narratives mediated by their cultures.